Reduced connexin-43 expression in the aorta of prehypertensive rats - Dlugošová, Katarína; Mitašíková, M; Bernátová, Iveta; Weismann, Peter; Okruhlicová, Ľudmila (Physiological research, 2008)
Genetic component represents an important factor in the development of hypertension, which is known to be associated with changes in expression of vascular gap junction protein connexin 43 (Cx43). The aim of the study was to examine the distribution and expression of Cx43 in the aortic endothelium of adult normotensive Wistar rats (W), borderline hypertensive rats (BHR) and spontaneously hypertensive rats (SHR). Rings of the thoracic aorta were processed for immunofluorescence and Western blot analysis of endothelial Cx43 and for electron microscopy. Both, BHR and SHR exhibited significantly increased blood pressure vs. W (132+/-2 mm Hg and 185+/-3 mm Hg vs. 110+/-2 mm Hg). Reduced Cx43 immunofluorescence was observed in the endothelium of BHR and these alterations were more pronounced in SHR. Western blot analysis showed significant suppression of Cx43 expression in the aorta of both BHR (p<0.05) and SHR (p<0.001) vs. W. Electron microscopy revealed local subcellular alterations of interendothelial connections in BHR including extended tight junctions. These alterations were more frequent and marked in SHR. The results indicate that connexin 43 expression is reduced in the aortic endothelium already in prehypertensive period, which may affect cell-to-cell communication and thus participate in acceleration of hypertensive disease.
Keywords: modely nemocí na zvířatech; Animals; Down-Regulation; krysa rodu Rattus; Disease Progression; Endothelium, Vascular; Fluorescent Antibody Technique; mužské pohlaví; Hypertension; Rats, Inbred SHR; krevní tlak; down regulace; transmisní elektronová mikroskopie; aorta thoracica; Blood Pressure; konexin 43; potkani inbrední SHR; Rats; Male; Disease Models, Animal; Connexin 43; zvířata; progrese nemoci; cévní endotel; Microscopy, Electron, Transmission; Aorta, Thoracic; potkani Wistar; western blotting; těsný spoj; Rats, Wistar; hypertenze; Blotting, Western; Tight Junctions; fluorescenční protilátková technika